Temporal settlement patterns and size at transition of the juvenile cod (Gadus morhua), haddock (Melanogrammus aeglefinus) and whiting (Merlangius merlangus) in the northern North Sea ... - Demain, Dorota K.; Gallego, Alejandro; Millar, Colin; Priede, Imants G.; Jones, Emma G. (ASC 2011 - Theme session H, 2024)
No abstracts are to be cited without prior reference to the author.Cod, haddock, and whiting are among the most economically important species in the Scottish demersal fishery. Juvenile settlement, the transition from pelagic to demersal habitat, has been identified as an important milestone for these species, but there is insufficient knowledge and data on this life stage. It is believed that the period of settlement has an impact on recruitment success, as important density‐dependent processes may take place, such as competition for suitable substrate, refuge or prey. Also, knowledge of settlement timing and duration is relevant to understanding population connectivity and thus to the development of successful conservation measures. Sampling was conducted between April and August 2004, June and September 2005, and June and July 2006 at an inshore site off the east coast of Scotland. Over 4000 0‐group cod, haddock, and whiting were collected. The results demonstrated that the transition from the pelagic to ...